Automated collegiate faculty performance evaluation system for College of Computer Studies of National University with DSS for tasking - Azucena, Jonises V.; Bumanlag, Mark S.;Dicatanongan, Linn Mar O.;Agati, Tobby Tom (Manila : National University, 2013)
"Performance assessment is the process of evaluating individuals according to the evaluator's determined criteria over upon their job performance. It measures their standings and efforts to determine their strengths and weaknesses in their field of work fields. Performance assessment is commonly used as a devised in business companies to comprehend and managed their employees' and co-workers' performance to measure their capacity in work and their different capabilities. Thus results gained from it are the basis of the employees' salary accounting calculations, ranking, incentives, and promotion system."--Introduction.
Title page -- Recommendation -- Summary -- Table of contents -- Chapter 1 Introduction -- Chapter 2 Conceptual framework -- Chapter 3 Methodology -- Chapter 4 System presentation -- Chapter 5 Implementation issues.
Includes bibliographical references.
Keywords: EVALUATION SYSTEMS